Population ecological traits of Tursiops truncatus putative morphotypes in the transitional region of the Mexican Pacific Ocean - Viloria-Gómora, Lorena; Medrano González, Luis (THERYA, 2015)
Introduction: The bottlenose dolphin (Tursiops truncatus) exhibits high morphological and ecological variation not yet resolved for intraspecific systematics and population identity. Different non-well defined morphotypes of this species are often sympatric in the transitional realm between the East Tropical Pacific, the Gulf of California and the East North Pacific. In order to gain insights about the relationship between morphological variation and population identity of bottlenose dolphins in this transitional region, we surveyed the Bahía de Banderas and its surroundings making a heuristic identification of putative morphotypes from size and coloration classes and examined the correspondence of the determined forms with ecological traits indicative of population identity. Methods: We navigated a transect-set of 20,641 km between years 2003 and 2005 covering an area of ca. 2500 km2 in which we recorded 170 sightings and achieved 302 photographic identifications of 207 bottlenose dolphins. We examined and classified the variation of 18 ecological traits that include spatial and seasonal distribution of abundance, seasonal patterns of pod size and calving as well as dispersion parameters obtained from mark-recapture data. Results: We determined five putative morphotypes of which the small light-gray (GCP), the large light-gray (GCG) and the large dark (GOG) occurred regularly in the region. These morphotypes exhibited distinctive, though overlapped, geographic and seasonal distributions as well as different, though related, patterns of pod size, calving and dispersion. A classification analysis indicated an equidistant separation between the three forms being GCG intermediate between GCP and GOG. Discussion: Our results suggest a model of a metapopulation with partially differentiated units determined by the narrow bounds between pelagic and coastal environments. A local conservation policy focused on bottlenose dolphins is needed for the apparently resident GCP form and its environment as well as for phylopatric animals of other forms and population affinities that may extend conservation benefits beyond Bahía de Banderas. Key words: Calving; dispersion; mark-recapture method; metapopulation; pod size; spatial distribution; seasonal distribution; transects method